Corporatisme paradigmatique, théories déontologiques et nouvel ordre mondial - Giesen, Klaus-Gerd (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1993)
This article begins by pointing out the discrepancy between, on the one hand, a certain political discourse which refers to a so-called New World Order in highly moralistic terms and, on the other hand, brute facts which attest to the contrary (resurgence of violent regional conflicts, atomization of global structures). It then examines the possibilities for analysing this discrepancy from a critical perspective centered on ethical norms. This leads the author to review the principal ethical approaches elaborated within the study of international relations since the Second World War. Emphasis is put on a major epistemological cleavage between academic disciplines, perhaps the most important demarcation in ethical theory : the one separating deontological from non-deontological theories. The systematic rejection or marginalization of deontology by the « discipline » of International Relations can be explained in terms of objective cognitive interests which have established, paradigmatically a genuine spirit of corporatism within the discipline. This article endeavors to explain such corporatism with a view to helping start a truly pluridisciplinary debate on ethics in the post-cold-war era